Retiring rail (Raton Range Raton, New Mexico, 1986)
Newspaper Article on the retirement of Clyde Barnes from the Santa Fe Railroad.
Master list item #: 12
File location is in the Raton File Cabinet
Keywords: Barnes, Clyde; Barnes, Virginia; Santa Fe Railroad; Local History; Biography; Life and Customs; Railroad; Retirement; Raton, New Mexico